Theoretical computer science 7th IFIP TC 1/WG 2.2 International Conference, TCS 2012, Amsterdam, The Netherlands, September 26-28, 2012. Proceedings - Ball, Tom; Boer, Frank S.; Baeten, Jos C. M. (Lecture Notes in Computer Science,, 2012)
This book constitutes the refereed proceedings of the 7th FIP WG 2.2 International Conference, TCS 2012, held in Amsterdam, The Netherlands, in September 2012. The 25 revised full papers presented, together with one invited talk, were carefully reviewed and selected from 48 submissions. New results of computation theory are presented and more broadly experts in theoretical computer science meet to share insights and ask questions about the future directions of the field.